Dietary Supplementation of Moringa oleifera Leaf Extract as a Prebiotic for Improved Growth in Nile Tilapia (Oreochromis niloticus) - Aprililianti Aprililianti; Wastu Ayu; Nunik Cokrowati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Functional feed additives from plant sources are increasingly explored to improve aquaculture efficiency and sustainability. This study was conducted to assess the influence of dietary Moringa oleifera leaf extract supplementation as a natural prebiotic source on the growth performance and feed utilization efficiency in Nile tilapia (Oreochromis niloticus). The experiment was carried out for a period of 40 days in a completely randomized design with four dietary treatments of moringa leaf extract levels, controlling (0), 10, 15 and 20 mL/100 g diets, each replicated three times. The performance criteria were survival rate (SR), absolute weight and length gain, specific growth rate (SGR), feed conversion ratio (FCR), feed utilization efficiency (EPP) and water quality. Results indicated that there are no significant effects of M. oleifera leaf extract supplementation SR, absolute weight gain, absolute length gain and SGR (p > 0.05) however it significantly affects FCR and EPP (p < 0.05). The lowest FCR and the highest EPP were observed in fish fed 20 mL/100 g feed, which suggests a better utilization of the feed. All water quality parameters were adequate during the culture period. In conclusion, M. oleifera leaf extract has potential as a natural feed additive with prebiotic-like properties to enhance feed efficiency in Nile tilapia, thereby supporting more efficient and sustainable aquaculture practices.